PERBEDAAN ICHININSHO DAIMEISHI MENURUT GENDER - CUK YUANA (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
The variety of languages can be traced in every language. However from gender point view, it seems that every language does not have any differences. The different choice of vocabulary or goi used by men and women can be classified in Futsuu Meishi (noun), Ichininsho Daimeshi (first person pronoun), and Sanninsho Daimeishi (third person pronoun). This research focuses on futumeishi and Ichininsho Daimeishi. In futsumeishi, female speakers tend to add the prefix "O" or "GO" in front of meishi which is meant to respect, while male speakers tend not to use the prefix "O" or "GO". In Ichininsho daimeishi, male speakers tend to choose and use vocabulary that seems more crude, namely "washi, boku, ore, etc.", while female speakers tend to choose and use vocabulary that seems more subtle, such as "watakushi, atakushi, atashi, and so on.â€ Keywords: language variety, gender, male language, female language, koyumeishi